Analysis of Violations of the Advertising Code of Ethics in Advertising Spotify “Listening Is Everything” - Ismianti, Rahma; Putri, Elmalia; Lutfia, Ashri; KN, Jamiati (Educationist: Journal of Educational and Cultural Studies, 2023)
As the development of media and technology has placed it as the leading media in transformation and communication, advertising has also increased, one of which is in advertisements that air through TVC media. Spotify is a company that makes advertisements through TVC with the title "Listening is Everything" for 15 seconds. Spotify's goal in airing the ad is to increase brand awareness and attract the attention and interest of audiences who have not used Spotify as an application to listen to songs. But in the ad, some scenes violated the code of ethics in the Indonesian Pariwara Ethics. So, in this study, researchers will discuss the Spotify ad version "Listening is Everything" according to the ethics of advertising and the Indonesian Pariwara Ethics because ethics have a vital role in communication. The methods used are observation and documentation. The findings of the research on Spotify advertisements in 2022, which are 15 seconds long, show two scenes that violate Indonesian Advertising Ethics. An advertisement must be based on Indonesian Advertising Ethics so the ad is produced correctly.